What oral cavity can show in COVID-19 patients? Literature integrative review (Research, Society and Development, 2021)
COVID-19, a pandemic disease, does not have its pathogenesis completely clarified although it is a polysystemic infection that may even present oral manifestations, due to the ability of the SARS-CoV-2 virus to bind to the angiotensin-converting enzyme 2 (ACE-2). This integrative literature review aims to identify the main oral manifestations of SARS-CoV2 virus infection and seek to establish whether or not there is a relationship between the appearance of oral manifestations and the systemic condition and prognosis of this patient. To perform this work, the Pubmed database was used, with the selection of 11 articles, after applying the inclusion and exclusion criteria, based on the PRISMA-ScR strategy for qualitative analysis. The results show that the most prevalent oral manifestations associated with COVID-19 are oral candidiasis and ulcerated lesions, but herpetic lesions, desquamative gingivitis, necrotizing periodontitis, among others, can also occur. In addition, they present taste impairment as the most common symptom, with dysgeusia being the most prevalent. And although some researchers already report an association between more severe manifestations of the disease and dissemination of oral lesions, more clinical and randomized studies are needed to definitively elucidate the relationship between oral manifestations and the prognosis of the systemic syndrome of COVID-19.